2019
DOI: 10.29252/jafm.12.03.29245
|View full text |Cite
|
Sign up to set email alerts
|

Steady Flow of Purely Viscous Shear-Thinning Fluids in a 1:3 Planar Gradual Expansion

Abstract: Laminar flow of non-Newtonian fluid (shear-thinning) through a 1:3 planar gradual expansion is numerically investigated, for various Power-Law index (0.6, 0.8 and 1.0) and expansion angles (15, 30, 45, 60 and 90°) at different generalized Reynolds number (1 ≤ Reg ≤ 400). The study of these parameters effect on the flow pattern allowed the determination of the two critical generalized Reynolds numbers (Regcr1 and Regcr2), which correspond to the transition from the symmetric to the asymmetric flow and the appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Flow through a sudden expansion channel is a well-known phenomenon [Mostafavi et al (2017)]. Many authors [Mostafavi et al (2017); Menouer et al (2019)], experimentally and numerically, have shown that the increase in Re causes the existence of two or more flow separation zones at the lower and upper corner walls, which causes a substantial heat loss [Galuppo et al (2017)]. Hilo et al (2020) studied different properties of the hydrothermal phenomena of flow over a suddenly expanded channel.…”
Section: Nomenclaturementioning
confidence: 99%
“…Flow through a sudden expansion channel is a well-known phenomenon [Mostafavi et al (2017)]. Many authors [Mostafavi et al (2017); Menouer et al (2019)], experimentally and numerically, have shown that the increase in Re causes the existence of two or more flow separation zones at the lower and upper corner walls, which causes a substantial heat loss [Galuppo et al (2017)]. Hilo et al (2020) studied different properties of the hydrothermal phenomena of flow over a suddenly expanded channel.…”
Section: Nomenclaturementioning
confidence: 99%